Evaluating a multiplier approach to coach education within the German Football Association's talent development program: an example of an intervention study targeting need-supportive coaching - Wachsmuth, S.; Raabe, J.; Readdy, T.; Dugandzic, D.; Höner, O. (International Sport Coaching Journal, 2022)
Coaches are among the most important agents for young football talents` development. Their coaching style may impact not only players` skill acquisition but also their motivation to meet their full potential. This study begins by presenting an intervention promoting need-supportive coaching to facilitate holistic talent development within the German Football Association (Deutscher Fußball-Bund [DFB]). The intervention was grounded in Deci and Ryan`s self-determination theory and designed as a hybrid model of coach education (i.e., online and in-present elements). In addition, DFB competence center coordinators were utilized as multipliers to reach a large population of approximately 1,300 coaches across Germany. The specific aim of this paper is to examine how these coordinators experienced the development and implementation process of the intervention. Utilizing a mixed-methods approach, coordinators` satisfaction and experiences with the intervention were evaluated via a quantitative online survey (n = 23) and qualitative follow-up interviews (n = 8). Overall, the findings suggest that the presented approach may be suitable to address potential barriers in coach education, such as gaining coaches` buy-in, transferring scientific knowledge into practice, and supporting long-term behavioral modifications in coaches. Specific recommendations (e.g., knowledge translation, gaining buy-in) for designing future interventions are highlighted.